Endoscopic approach to fourth ventricle cysticercosis - Samuel Tau Zymberg; Manoel Antonio Paiva Neto; Alessandra A.P. Gorgulho; Sérgio Cavalheiro (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis is the most frequently observed parasitosis of the central nervous system worldwide. The fourth ventricle is the most frequent site of intraventricular infestation, a location that carries a higher risk for CSF blockage and intracranial hypertension due to CSF blockage. A great number of patients become shunt dependent which carries a poorer prognosis. We report on a case of a patient with symptomatic obstructive hydrocephalus due to cysticercus in the fourth ventricle where an endoscopic approach via a frontal burr hole was performed. Although there is no consensus in the literature for the optimal treatment of this disease, this method seemed adequate for treatment of fourth ventricle cysticercosis in patients with hydrocephalus, aqueductal and foramen of Monro dilatations.